2006
DOI: 10.1111/j.1600-0501.2005.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival in mandibles of irradiated oral cancer patients

Abstract: Radiation therapy with 50 Gy was significantly related to shorter implant survival in mandibular bone. Survival was lowest in grafted bone. Time of implant placement had no statistically significant influence on survival under the conditions of this study. Although implant survival is lower in irradiated mandibles, implants significantly facilitate prosthodontic treatment and enhance outcome of oral rehabilitation in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
168
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(187 citation statements)
references
References 32 publications
11
168
1
7
Order By: Relevance
“…Deterioration of the bone microstructure due to, eg, osteoporosis, radiation therapy, or systemic treatment with bisphosphonates is frequently encountered in the clinic and, with respect to maxillofacial and orthopedic surgery, might affect the survival rate of Ti implants. 6,7,44 Noble et al reported on an insufficient fit of cementless femoral prostheses, 51 while Moritz et al pointed out the possible risk of implant migration in poor bone quality. 52 Buddula et al describes a greater risk of implant failure, when placed in irradiated bone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deterioration of the bone microstructure due to, eg, osteoporosis, radiation therapy, or systemic treatment with bisphosphonates is frequently encountered in the clinic and, with respect to maxillofacial and orthopedic surgery, might affect the survival rate of Ti implants. 6,7,44 Noble et al reported on an insufficient fit of cementless femoral prostheses, 51 while Moritz et al pointed out the possible risk of implant migration in poor bone quality. 52 Buddula et al describes a greater risk of implant failure, when placed in irradiated bone.…”
mentioning
confidence: 99%
“…These patients are running a higher risk of implant failure, especially when the implant is placed in grafted bone. 6 On that account, irradiated animals could serve as models for experimental setups in order to gain knowledge about the performance of implant surfaces, functionalized …”
mentioning
confidence: 99%
“…L'ensemble des auteurs retrouve un taux d'échec plus important au maxillaire qu'à la mandibule [25][26][27] (taux de survie des implants de 59 % au maxillaire contre 85 % à la mandibule selon Visch et al [25] et de 57,1 % contre 98,4 % pour Sammartino et al [28]). Une dose d'irradiation de 50 Gy est communément admise comme étant le seuil au dessus duquel la fréquence d'échec implantaire augmente de façon significative [28][29][30]. Le taux d'échec est similaire en terrain non irradié ou irradié lorsque la dose d'irradiation est inférieur à 45 Gy [25,31].…”
Section: Intérêt De L'implantologie Chez Le Patient Irradiéunclassified
“…Dans une brochure intitulée « la reconstruction du visage après un cancer », éditée récemment par la Ligue contre le cancer à destination du grand public, il est fait mention de la possibilité de mise en place d'implants dentaires, notamment pour stabiliser un dispositif prothétique [97]. Les bénéfices de l'implantologie sont tels pour le patient que le rapport béné-fice/risque penche le plus souvent en faveur du bénéfice apporté par le recours aux implants dentaires [24,30,36,37]. Toutefois, on doit noter que de nombreux cancérologues estiment encore que la mise en place d'implants en terrain irradié, même sous couvert d'une oxygénothérapie hyperbare, reste toujours formellement contre-indiquée [38].…”
Section: Intérêt De L'implantologie Chez Le Patient Irradiéunclassified
See 1 more Smart Citation